Acesso à justiça para a população em situação de rua: um desafio para a defensoria pública - Ribas, Luciana Marin (2014)
Considered a theoretical framework on the subject, the report on access to justice by Mauro Cappelletti and Bryant Garth, published in the last 1970s, encouraged the development of research regarding the justice system in western democracies, including Brazil. From this context, this dissertation aims to explore further the issue of access to justice, combining theory to practice by presenting the existing institutional tools. The present study is devoted to a theoretical research on the subject and to the exposure of a crisis in the national judicial system. With so many procedural reforms insufficient to deal with this crisis, this work argues that the term "access to justice" cannot be interpreted restrictively as "access to the courts" and proposes a "new justice" model for the Brazilian reality. The proposal involves the study of the Public Defender's Office, the institution responsible to ensure legal assistance to those most distant from the justice system: social or Judiciary. From this context, the dissertation methodology evolves to study a project developed in the city of São Paulo commited to provide legal services for the homeless population; this part of the work demanded field research and interviews with the people involved with the project. The case study is able to demonstrate how theory and practice are still far apart and how troubled is the path that leads to an effective access to justice as proposed in this work